2022
DOI: 10.3389/ti.2022.10839
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Monotherapy is Safe in Immunologically Low-Risk Kidney Transplant Recipients: A Randomized-Controlled Pilot Study

Abstract: In this randomized-controlled pilot study, the feasibility and safety of tacrolimus monotherapy in immunologically low-risk kidney transplant recipients was evaluated [NTR4824, www.trialregister.nl]. Low immunological risk was defined as maximal 3 HLA mismatches and the absence of panel reactive antibodies. Six months after transplantation, recipients were randomized if eGFR >30 ml/min, proteinuria <50 mg protein/mmol creatinine, no biopsy-proven rejection after 3 months, and no lymphocyte deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Recently, it was shown in a small RCT that immunologically low-risk elderly recipients could be safely managed with tacrolimus monotherapy one year after transplantation. The results showed significantly fewer infections and a much better COVID vaccination response while medication adherence improved with fewer gastro-intestinal side effects [24]. Though these results indicate that the aged immune system of the elderly allows for and benefits from less intense immune suppression, confirmation in a larger study is required.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, it was shown in a small RCT that immunologically low-risk elderly recipients could be safely managed with tacrolimus monotherapy one year after transplantation. The results showed significantly fewer infections and a much better COVID vaccination response while medication adherence improved with fewer gastro-intestinal side effects [24]. Though these results indicate that the aged immune system of the elderly allows for and benefits from less intense immune suppression, confirmation in a larger study is required.…”
Section: Discussionmentioning
confidence: 91%
“…In a recent study, immunological low-risk patients, of whom the majority were elderly, were randomized for continuing standard immune suppression vs. tacrolimus monotherapy at 1 year after transplantation [34]. This feasibility study showed that after discontinuation of MMF, DSA remained undetectable for at least 4 years, infections were reduced, and vaccination responses to SARS-CoV-19 were superior [35].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent pilot study, researchers from Erasmus Medical Centre in the Netherlands investigated the ability to withdraw MMF in low immunological-risk recipients by 9 months following renal transplant [ 4 ]. A pre-planned sub-study investigated responses to the pneumococcal, tetanus and influenza vaccines at 12-month post-transplant [ 5 ].…”
Section: Clinical Impact Summarymentioning
confidence: 99%